In vitro tolerance of Rubus spp. cultivars to mannitol-simulated drought stress - Millones, Carlos (2021)
Introduction. The characterization of hydric drought stress tolerant cultivars of Rubus spp. in experimental fields is complicated by the difficulty of controlling the external factors of the environment where they are installed. In vitro stress induction is an efficient tool to study plant response mechanisms and is used in breeding programs for the selection of hydric drought stress tolerant genotypes. Objective. To evaluate the in vitro morphological and physiological response of explants in three cultivars and the wild accession of Rubus spp. under mannitol-simulated hydric drought stress conditions. Materials and methods. The study was carried out in the Biology Laboratory of Universidad Nacional Toribio Rodríguez de Mendoza de Amazonas, Peru, during the year 2020. A completely randomized design with factorial arrangement (Factor A: four genotypes and Factor B: simulated water potentials with mannitol: 0, -0.2, -0.3, and -0.4 MPa) and four explants per experimental unit were used. Results. The cultivars responded differently under mannitol-simulated hydric drought stress. The Navaho and Tupy cultivars registered higher tolerance. Conclusion. The morphological and physiological traits related to the root length, the water content of the shoot, root and leaf allowed to identify Rubus spp. cultivars tolerant to mannitol-simulated hydric drought stress in the vegetative phase.